1998
DOI: 10.1111/j.1600-0773.1998.tb01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Styrene and Styrene Oxide‐Induced DNA Damage in Various Organs of Mice Using the Comet Assay

Abstract: Styrene (100-500 mg/kg b.wt.) and styrene oxide (50-200 mgikg b.wt.) were given as a single intraperitoneal injection to female mice (C57BLi6) at various time intervals before sacrifice. Primary DNA damage in various organs was studied using alkaline single cell gel electrophoresis (comet) assay. Both substances induced significant DNA damage in lymphocytes, liver, bone marrow and kidney after 4 hr. The lymphocytes and liver cells were found to be the most sensitive cells to the DNA damaging effects of both ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 31 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…We briefly describe two in vivo studies. Vaghef and Hellman () used a single i.p. injection of styrene or SO to expose female B57BL/6 mice.…”
Section: Critical Review Of the Individual Studies For Styrene/somentioning
confidence: 99%
“…We briefly describe two in vivo studies. Vaghef and Hellman () used a single i.p. injection of styrene or SO to expose female B57BL/6 mice.…”
Section: Critical Review Of the Individual Studies For Styrene/somentioning
confidence: 99%
“…Thus, one of the conclusions would be that SO-induced DNA adducts in vivo is an indicator of the potential genotoxicity of styrene. Yet, results of the studies reported here using the most rigor- (Vaghef & Hellman, 1998) and in bone marrow/lymphocytes of mice exposed via inhalation (up to 21 days) to styrene (Vodicka et al, 2001), although these studies pre-dated the publication of internationally accepted protocols for their conduct.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several other in vivo studies that also reported negative results for MN induction following inhalation exposure to styrene or SO, the study by Gate et al is particularly relevant to the results of the current study given the similarity in the duration of exposure and adherence to the test guidelines. It should be mentioned that DNA strand breakage was reported in various organs of mice following intraperitoneal administration of styrene or SO (Vaghef & Hellman, 1998) and in bone marrow/lymphocytes of mice exposed via inhalation (up to 21 days) to styrene (Vodicka et al, 2001), although these studies pre‐dated the publication of internationally accepted protocols for their conduct.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DNA adducts were found in several tissues such as the liver and lung in rodent studies [ 54 , 70 73 ]. Regarding other in vivo assays, the comet assay in the liver tissue of mouse showed positive results [ 74 , 75 ]. Our findings show that mutagenic effects were not observed in the lungs of mice that gavaged styrene at a carcinogenicity level [ 48 ] of 300 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%